Study of salivary α-amylase immunoglobulin, a and flow rate in diabetic subjects: a cross sectional study - Patel, Dinesh C.; Thakkar, Jiger M. (International Journal of Research in Medical Sciences, 2022)
Background: Diabetes is possibly the mainly common metabolic syndrome with salivary inference. However, lack of literature on the possible relationship between diabetes and salivary α-amylase, Immunoglobulin-A (IgA) and flow rate. Therefore, present study aims to estimate of salivary α-amylase, immunoglobulin-A and flow rate in diabetic subjects of Indian population. Methods: The present cross sectional study was done on 60 subjects of diabetes mellitus (T2DM) and 60 subjects’ non-diabetic healthy controls at Banas medical college and our hospital. The subject’s demographic and anthropometric parameters were recorded; detailed history and clinical examination were performed in the entire cases. The un-stimulated saliva was collected in the fasting state. Salivary flow rate, biochemical variables and IgA were analyzed. Data which was collected was statistically analyzed. Results: The results showed that salivary glucose (p<0.001) and urea levels (p<0.001) were significantly higher in diabetic patients compared with non-diabetic subjects. It was also found that the diabetic patients had significant reduction in salivary flow rate (p<0.01), α- amylase (p<0.001) and total protein levels (p<0.05) when compared with non-diabetic individuals. In contrast, there was no significant difference was observe in levels of IgA (p>0.05) between diabetic and non-diabetic subjects. Conclusions: In our study, we conclude that significant differences were reported in salivary flow rate, α-amylase and IgA between diabetics and non diabetics. Therefore, we suggested that estimation of salivary parameters might be a cost effective and a non invasive choice for screening, diagnosis and monitoring of diabetes instead of blood.